Pengaruh model pembelajaran student teams achievement divisions berbantuan game pada aplikasi wordwall terhadap hasil belajar matematika materi bilangan cacah ditinjau dari motivasi belajar - Tarinda Isnindya Sari; Riyadi Riyadi; Siti Wahyuningsih (Universitas Sebelas Maret, 2025)
The three goals of this study are: 1) compare the learning outcomes of students taught with the STAD learning model assisted by games on Wordwall application with taught with direct learning models; 2) compare the learning outcomes of students with high and low learning motivation; and 3) ascertain the interaction between learning models and learning motivation on student learning outcomes. The population of this study consisted of fifth-grade students from public primary schools in the Foster Area III Grogol sub-district. Using the cluster sampling technique, two elementary schools were selected to serve as the research sample. The methoda for gathering data involved questionnaires and tests. The two-way anava technique was used to analyze the data in this study. The findings of the study are: 1) students who receive instruction using the STAD learning model with games on the Wordwall application have different learning outcomes with students who receive instruction using direct learning models; 2) there is no significant difference in the learning results of student with high and low learning motivation; and 3) regarding student learning outcomes, there is no interaction between learning models and learning motivation.